Piecewise Sparse Recovery via Piecewise Inverse Scale Space Algorithm with Deletion Rule (Journal of Computational Mathematics, 2020)
In some applications, there are signals with piecewise structure to be recovered. In thispaper, we propose a piecewise_ISS (P_ISS) method which aims to preserve the piecewisesparse structure (or the small-scaled entries) of piecewise signals. In order to avoid selectingredundant false small-scaled elements, we also implement the piecewise_ISS algorithm inparallel and distributed manners equipped with a deletion rule. Numerical experimentsindicate that compared with aISS, the P_ISS algorithm is more effective and robust forpiecewise sparse recovery.
Keywords: Inverse scale space; Piecewise sparse; Sparse recovery; Small-scaled entries.